2023
DOI: 10.1002/app.54763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maleic anhydride on the moisture crosslinking of EVM‐GMA grafted with amino silane

Yupeng Su,
Kehui Han,
Martin Hoch
et al.

Abstract: Moisture crosslinking would be a good substitution to cure ethylene‐vinyl acetate‐glycidyl methacrylate rubber (EVM‐GMA) due to the characteristics of low cost and environmental friendliness. Our previous study found amino silane grafted onto EVM‐GMA with low degree due to the low epoxy group content in rubber matrix. Consequently, the moisture crosslinking density of rubber compound is low. So, it is necessary to find an effective method to improve the moisture crosslinking density of EVM‐GMA. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The tailored microstructure depends largely on the present functional group, interfacial interactions, [17] and processing parameters of the polymers. [18], [19] Other studies have also shown that the molecular weight and gel content of thermoplastics, [13], [14] TPEs, [19] and rubber blends [20] expand in proportion to the amount of MA grafting. The crosslink polymer chains were connected by the MA ring opening linkage at the active site of the surrounding neighbourhood chain.…”
Section: Introductionmentioning
confidence: 99%
“…The tailored microstructure depends largely on the present functional group, interfacial interactions, [17] and processing parameters of the polymers. [18], [19] Other studies have also shown that the molecular weight and gel content of thermoplastics, [13], [14] TPEs, [19] and rubber blends [20] expand in proportion to the amount of MA grafting. The crosslink polymer chains were connected by the MA ring opening linkage at the active site of the surrounding neighbourhood chain.…”
Section: Introductionmentioning
confidence: 99%